Review of Junaid Al-Baghdadi's Sophistic Economic Thoughts - Havis Aravik; Achmad Irwan Hamzani; Nur Khasanah (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2023)
This study aims to determine Junaid al-Baghdadi's sufistic economic thought. This research is included in qualitative research based on field data. Qualitative descriptive analysis technique that focuses on content analysis. The results show that Junaid al-Baghdadi is one of the Sufi figures in Islam whose thoughts outside of Sufism have contributed greatly to the development and study of Islamic economics. Mitsaq's trilogy of thought, Fana' and Tawhid are very important as a way for people to get close to Allah in their various worship activities, including in the economic field. Because Junaid, like other Islamic economic thinkers, believes that doing business to seek sustenance is part of worshiping Allah. Economic motives must be oriented towards Allah's pleasure, and bring about maslahah, not mafsadah. So that they can be held accountable later in the hereafter and get blessings.